Pewarisan Karakter Hasil dan Komponen Hasil pada Dua Populasi Persilangan Cabai Rawit Hijau (Capsicum annuum L.) - Yudilastari, Tiara; Syukur, Muhamad; Sobir, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Genetic information plays an important role in plant selection. This research was aimed to obtain genetic information on pattern inheritance of yield and yield component characters of two crosses population of birds chili. The research used biparental mating design consisted of 40 plants of parents population (P1 and P2), 40 plants of first generation (F1) and reciprocal (F1R) populations, 100 plants of backcross populations (BCP1 and BCP2), and 300 plants of second generation population (F2). Scaling test and joint scaling test indicated the presence of gene interaction (epistasis) in two crosses population. Estimates gene effect also showed that fruit weight character in crosses population of IPB C145 x IPB C174 was controlled by duplication epistasis, while yield per plant character in crosses population of IPB C145 x IPB C291 was controlled by complementary epistasis. All characters of both crosses populations had high broad sense heritability, but the characters in crosses population of IPB C145 x IPB C174 had medium to high narrow sense heritability, while the characters in crosses population of IPB C145 x IPB C291 had low to medium narrow sense heritability. Genetic difference between parents seemed to affect gene action of a character, in which yield per plant, number of fruits per plant, fruit weight, and fruit length characters in crosses population of IPB C145 x IPB C291 with small genetic difference were more controlled by the action of non additive gene than crosses population of IPB C145 x IPB C291 with large genetic difference.Keywords: epistasis, gene action, genetic difference, heritability, yield